Should relational effects be considered in health care priority setting? - Gustavsson, Erik; Juth, Niklas 1973-; Lärfars, Gerd; Raaschou, Pauline; Sandman, Lars (2023)
It is uncontroversial to claim that the extent to which health care interventions benefit patients is a relevant consideration for health care priority setting. However, when effects accrue to the individual patient, effects of a more indirect kind may accrue to other individuals as well, such as the patient's children, friends, or partner. If, and if so how, such relational effects should be considered relevant in priority setting is contentious. In this paper, we illustrate this question by using disease-modifying drugs for Alzheimer's disease as a case in point. The ethical analysis begins by sketching the so-called prima facie case for ascribing moral weight to relational effects and then moves on to consider a number of objections to it. We argue that, whereas one set of objections may be dismissed, there is another set of arguments that poses more serious challenges for including relational effects in priority setting.
Keywords: significant others; priority setting; need-based health care; indirect effects